The male pachynema-specific protein MAPS drives phase separation in vitro and regulates sex body formation and chromatin behaviors in vivo - Zexiong Lin; Dongliang Li; Jiahuan Zheng; Chencheng Yao; Dongteng Liu; Hao Zhang; Haiwei Feng; Chunxu Chen; Peng Li; Yuxiang Zhang; Binjie Jiang; Zhe Hu; et al. (Cell Reports, 2024)
Summary: Dynamic chromosome remodeling and nuclear compartmentalization take place during mammalian meiotic prophase I. We report here that the crucial roles of male pachynema-specific protein (MAPS) in pachynema progression might be mediated by its liquid-liquid phase separation in vitro and in cellulo. MAPS forms distinguishable liquid phases, and deletion or mutations of its N-terminal amino acids (aa) 2−9 disrupt its secondary structure and charge properties, impeding phase separation. Maps−/− pachytene spermatocytes exhibit defects in nucleus compartmentalization, including defects in forming sex bodies, altered nucleosome composition, and disordered chromatin accessibility. MapsΔ2–9/Δ2–9 male mice expressing MAPS protein lacking aa 2–9 phenocopy Maps−/− mice. Moreover, a frameshift mutation in C3orf62, the human counterpart of Maps, is correlated with nonobstructive azoospermia in a patient exhibiting pachynema arrest in spermatocyte development. Hence, the phase separation property of MAPS seems essential for pachynema progression in mouse and human spermatocytes.